2018
DOI: 10.1073/pnas.1712971115
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of charged excitons in electronically and morphologically homogeneous single-walled carbon nanotubes

Abstract: The trion, a three-body charge-exciton bound state, offers unique opportunities to simultaneously manipulate charge, spin, and excitation in one-dimensional single-walled carbon nanotubes (SWNTs) at room temperature. Effective exploitation of trion quasi-particles requires fundamental insight into their creation and decay dynamics. Such knowledge, however, remains elusive for SWNT trion states, due to the electronic and morphological heterogeneity of commonly interrogated SWNT samples, and the fact that transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(69 citation statements)
references
References 34 publications
9
60
0
Order By: Relevance
“…Global analysis of the transient decay dynamics reveals four time constants (Figure 7d): 0.6 ps (62%), 16.3 ps (30%), 408 ps (8%) and a fourth one that exceeds the limitation (>3 ns) of the instrument coverage. The processes observed at 0.6 and 16.3 ps were assigned to the exciton-exciton annihilation and singlet exciton recombination [63,[68][69][70]. However, the long-lived component (408 ps) was not observed previously.…”
Section: Polymer/swcnt Hybridsmentioning
confidence: 66%
See 1 more Smart Citation
“…Global analysis of the transient decay dynamics reveals four time constants (Figure 7d): 0.6 ps (62%), 16.3 ps (30%), 408 ps (8%) and a fourth one that exceeds the limitation (>3 ns) of the instrument coverage. The processes observed at 0.6 and 16.3 ps were assigned to the exciton-exciton annihilation and singlet exciton recombination [63,[68][69][70]. However, the long-lived component (408 ps) was not observed previously.…”
Section: Polymer/swcnt Hybridsmentioning
confidence: 66%
“…The SWCNT (•+)n transient state nature was confirmed by adding the chemical oxidant (0.5 mm K 2 IrCl 6 [60,61]. More recent studies have shown that, this ∼1150 nm band is related to exciton polaron species, i.e., excitons dressed in the Fermi sea of charge carriers; and due to this reason, both the so-called "electron polaron" and "hole polaron" share the same spectroscopic signatures at ∼1150 nm [62][63][64]. Transient absorption bands centered at 625-800 nm and 880-950 nm are assigned to the polymer radical anion (Figure 6b).…”
Section: Polymer/swcnt Hybridsmentioning
confidence: 84%
“…nicotinic acetylcholine receptor pore [33] and the mitochondrial outer membrane protein TspO [34], as well as helical or spherical virus capsids and cytoskeletal filaments. AFM imaging of various small molecules and polymers assembled into helical supramolecular arrangements which are widely used in chemistry, materials science and nanotechnology could, likewise, benefit from 3D surface reconstructions as AFM is widely used to characterise a wide range of such structures [35], for example polymer wrapped functionalised carbon nanotubes [36,37], Further developments could also lead to samples exhibiting different symmetries such as icosahedral viral capsids to be reconstructed. In conclusion, the approach reported here will facilitate the use of AFM for structural studies of individual molecules in complex populations, and for integrative structural biology analysis of single molecular assemblies and their assembly mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…There are some theoretical [1][2][3][4][5][6][7][8][9][10][11][12][13] and experimental [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] studies on the decay rates of the quasiparticle states in layered graphenes, Bernal graphite, and carbon nanotubes. The electron-electron (e-e) Coulomb scatterings, 1,2,4,5,33 as well as the electron-phonon (e-ph) scatterings, 1,4,[13][14][15][16][17][18]26,28,29,33 play critical roles in the decay rates (the mean free paths) of the excited electron/hole states, especially for the former.…”
Section: Introductionmentioning
confidence: 99%
“…The femtosecond pump-probe spectroscopies are very powerful tools in exploring the ultrafast relation of photoexcited electrons. They cover the time-resolved photoemission spectroscopy, [16][17][18]26,27,30,31 absorption/transmission/reectivity, [19][20][21][22][23][24][25]32 and uorescence spectroscopies, 11,12 in which their measurements are very useful in understanding the quasiparticle behaviors of the excited conduction electrons. Moreover, the energy distributions of the ARPES measurements could provide the inelastic scattering rates of the excited valence holes.…”
Section: Introductionmentioning
confidence: 99%